The Influence of Value Added Tax Literacy, Financial Literacy, and the Use of Digital Money on Generation Z's Consumptive Behavior in Surabaya - Nanda Sheyla Intan Sabrina; Mira Pramudianti (Journal of Industrial Engineering & Management Research, 2026)
The shift in people's transaction patterns from cash to digital payment systems, accompanied by an increase in Value Added Tax rates and the high intensity of consumption of Generation Z in Surabaya City, has the potential to influence the consumption patterns of this generation amidst the increasingly widespread phenomenon of consumptive behavior. This study aims to analyze the Influence of Value Added Tax Literacy, Financial Literacy and the Use of Digital Money on the Consumptive Behavior of Generation Z in Surabaya City, using the Theory of Planned Behavior and Consumer Behavior Theory as a theoretical basis. This study uses a quantitative approach with a survey method. Data were collected through the distribution of online Likert-scale questionnaires to 181 Generation Z respondents in Surabaya City selected using purposive sampling techniques, then analyzed using multiple linear regression assisted by SPSS. The results of the study show that Value Added Tax Literacy has no effect on Consumptive Behavior, while Financial Literacy and the Use of Digital Money each have an effect on the Consumptive Behavior of Generation Z in Surabaya City. It is concluded that financial literacy and the intensity of digital money use are more dominant in shaping the consumptive behavior of Generation Z compared to tax literacy, so that more contextual financial and tax education is urgently needed.